A fundamental study of the shearing stress of biological film in a trickling filter process - Gaspillo, Pag-asa Duran
A well established model for microbial growth in trickling filters has been used to study the effective hydraulic loading range and its corresponding shearing-stress that would develop and maintain an active biological film community for super-high rate operations. Two separate models were used, one is laboratory scale and the other is pilot-scale trickling filter. Experimental investigation for pilot scale were limited to hydraulic loading rates test at no bio-mass hold-up due to very limited time and that very low winter temperature in Tokyo, Japan (below 10°C) where the research was conducted, prohibited any microbial growth on filter media. However, values obtained from laboratory scale experimentation at different flow velocities of wastewater were interpreted for characterization of the bio-mass system for pilot scale experimentation. These values were based on constant BOD loading conditions within the range of 40 to 60 ppm.